How do I choose a principal investigator for my next postdoc? - Forrester, Nikki (Nature (London), 2025)
A computer scientist is struggling to trust their postdoctoral research adviser after negative experiences with the previous two. How do you find one that’s right for you? A computer scientist is struggling to trust their postdoctoral research adviser after negative experiences with the previous two. How do you find one that’s right for you?